Techno-Economic Evaluation of a Commercial c-Phycocyanin Extraction Process - Williams, Aqeel (Department of Chemical Engineering, 2025)
Growing health concerns over synthetically produced pigments have led to the development of natural pigment products from phycobiliproteins, a family of proteins found in cyanobacteria. One such phycobiliprotein is c-phycocyanin (cPC), a bright blue pigment that has already found widespread application in the food and pharmaceutical industries. It can also be used in the cosmetics industry, an application which has not been as extensively explored. Spirulina platensis (Spirulina), a cyanobacterium known for its relatively economical and easy cultivation, is a popular source for the production of cPC. The Centre for Bioprocess Engineering Research (CeBER) at the University of Cape Town (UCT) has patented a novel process for extracting and purifying cPC from Spirulina (Fagan-Endres et al., 2019). A manufacturer of raw materials for the cosmetics and consumer products industries in South Africa (anonymously referred to as ‘Company A' in this dissertation), possesses the necessary resources, expertise, and market access to establish a cPC extraction and purification process. The global market for cPC for cosmetics use, valued at $27 million in 2020 with a projected compound annual growth rate (CAGR) of 10%, presents a lucrative opportunity. Therefore, a detailed techno-economic analysis was conducted on three cPC extraction and purification processes to assess their commercial viability. Process 1 was the example process presented in the UCT patent and thus considered the base design. In this process, following liberation of the cPC into a buffer solution and separation of the cell debris, the cPC was purified using a PEG-MDX aqueous two-phase separation (ATPS) and an ammonium sulphate precipitation train before the product was dried. Process 2 was an extension of the base process design based on work done by Hockey (2022) and included an additional citrate-PEG ATPS at the start of the purification unit operations. Process 3 was another extension on the base process design based on further work done by Kadir (n.d.), Payne (2023) and Dunnett (n.d.). In this instance, an adsorption step using activated carbon and chitosan was used to purify the cPC leachate instead of an ATPS. As part of this research, process flow diagrams (PFDs) and mass balances were compiled for each process. The mass balance used specific unit operation performance parameters drawn from literature, previous and concurrent work to this research by Hockey (2022), Kadir (n.d.), Payne (2023) and Dunnett (n.d.), equipment technical data sheets, correspondence with equipment suppliers, and laboratory work. For the techno-economic analysis, equipment and raw material quotations were collected, and widely applied cost correlations from literature were used in a discounted cash flow analysis to calculate common economic indicators: the payback period (PB), net present value (NPV) and internal rate of return (IRR). The primary indication for profitability was taken as when the IRR is equal to or exceeds the investor's weighted average cost of capital (WACC). Centre for Bioprocess Engineering Research The baseline case techno-economic analysis was conducted at nominal values for input parameters, the most critical of which were a pilot-scale Spirulina input of 20 kg per batch, a Spirulina cPC content of 8 wt%, a cPC product price of 820 $/kg, a discount rate (WACC) of 19.5% and an operation period of four years. Baseline case results from the techno-economic analysis showed that only Process 2 demonstrated profitability, with Process 1, 2 and 3 reporting an IRR of 6.7%, 19.6%, and 15.3%, respectively. A sensitivity analysis revealed interesting process dynamics and highlighted the significance of batch time in profitability. A Monte Carlo analysis was conducted at a production scale of 200 kg per batch Spirulina input to understand further process dynamics in response to inherent variation in critical input parameters. Both of these analyses confirmed the profitability of Process 2, and showed how the profitability of Process 1 and 3 could be improved by increasing the scale and the cPC content in Spirulina, in particular. Furthermore, Process 3 was found to be the most resilient to variation in input parameters. Process 2 was excluded from further optimisation due to its high direct capital investment, raw material requirement and processability risk. Therefore, for Process 1 and 3, an optimisation opportunity was identified wherein batch times were reduced by staggering batches, thereby maximising equipment utilisation. This enhanced the profitability of Process 1 and 3, and revealed that Process 3 was more profitable than Process 1. Further analysis found the minimum profitable scale for Process 3 at a cPC price of 820 $/kg to be 65 kg Spirulina input per batch, producing 245 batches per year, and this scale would serve the estimated market opportunity of 1 120 kg cPC in the first year of operation. The minimum selling price at the production scale of 200 kg Spirulina input was found to be 680 $/kg, 17% less than the assumed market price. It is recommended that Process 3 is implemented at Company A for cPC production, due to the process' robustness and profitability, at a production scale of 65 kg Spirulina input per batch, to match the market opportunity of 1 120 kg cPC per year. Implementing Process 3 at Company A will enable the company to tap into the growing cosmetics cPC market, leveraging its competitive advantage and maintaining profitability. Finally, this dissertation recommends the need for future research into the synthesis and performance of a granular activated carbon-chitosan adsorbent, the scale-up of the adsorption column, and the evaluation of larger-scale centrifuges. These research areas are suggested as the adsorption step is a crucial part of the recommended Process 3, and it was assumed that granular activated carbon-chitosan was used, which is not yet widely available. Furthermore, performance of the adsorption column was assumed to remain constant during scale-up, which is not realistic over time. Additionally, it is imperative to confirm the performance of larger scale centrifuges using the materials used in Process 3, as the nature of the streams exiting these units was found to be sensitive to these units' performance.